Antiviral therapy improves overall survival in hepatitis C virus‐infected patients who develop diffuse large B‐cell lymphoma. Issue 11 (18th August 2016) - Hosry, Jeff; Mahale, Parag; Turturro, Francesco; Miranda, Roberto N.; Economides, Minas P.; Granwehr, Bruno P.; Torres, Harrys A.
Abstract : Chronic Hepatitis C virus (HCV) infection is associated with increased incidence of non‐Hodgkin lymphoma. Several studies have demonstrated regression of indolent lymphoma with antiviral therapy (AVT) alone. However, the role of AVT in HCV‐infected patients with diffuse large B‐cell lymphoma (DLBCL) is unclear. We therefore analyzed AVT's impact on oncologic outcomes of HCV‐infected patients (cases) who developed DLBCL. Cases seen at our institution (June 2004–May 2014) were matched with uninfected counterparts (controls) and then divided according to prior AVT consisting of interferon‐based regimens. We studied 304 patients (76 cases and 228 controls). More cases than controls had extranodal (79% vs . 72%; p = 0.07) and upper gastrointestinal (GI; 42% vs . 24%; p = 0.004) involvement. Cases never given AVT had DLBCL more refractory to first‐line chemotherapy than that in the controls (33% vs . 17%; p = 0.05) and exhibited a trend toward more progressive lymphoma at last examination compared to controls (50% vs . 32%; p = 0.09) or cases given AVT (50% vs . 27%; p = 0.06). Cases never given AVT had worse 5‐year overall survival (OS) rates than did the controls (HR, 2.3 [95% CI, 1.01–5.3]; p = 0.04). Furthermore, AVT improved 5‐year OS rates among cases in both univariate (median [Interquartile range]: 39 [26–56] vs. 16 [6–41] months, p = 0.02) and multivariate analyses (HR = 0.21 [95% CI, 0.06–0.69]; p = 0.01). This study highlights the negative impact of chronic HCV on survival of DLBCL patients and shows that treatment of HCV infection is associated with a better cancer response to chemotherapy and improves 5‐year OS. Abstract : What's new? Chronic infection with hepatitis C virus (HCV) can increase the risk of non‐Hodgkin lymphoma. Treatment with antiviral therapy (AVT) may improve outcomes for several types of lymphoma associated with HCV infection, but results have been controversial. In this study, the authors asked whether AVT could benefit HCV‐infected patients who developed diffuse large B‐cell lymphoma (DLBCL). They found that, while HCV infection seems to worsen DLBCL prognosis, AVT improved five‐year overall survival in these infected patients.